Measuring global financial market stresses - Jan J. J. Groen; Michael B. Nattinger; Adam I. Noble (Federal Reserve Bank of New York, 2020)
We propose measures of financial market stress for forty-six countries and regions across the world. Our measures indicate that worldwide financial market stresses rose significantly in March following the widespread economic shutdowns in the wake of the COVID-19 pandemic. However, hardly anywhere in the world did these March peaks in financial stresses reach those seen during the trough of the 2007-09 Global Financial Crisis. Since March, financial market conditions normalized rapidly with financial market stresses around average levels. We also show that our financial stress measures have predictive power for the near-term economic outlook across most parts of the world, with the exception of China. A structural Bayesian VAR analysis indicates that historically, financial stress shocks, irrespective of the source of the shock, have significant impact on global economic activity, but in particular that emerging market economies are usually hit more severely than advanced economies.
Keywords: C32; C51; E44; F30; F65; 330; financial markets; financial stress indices; emerging markets; advanced economies; SVAR